SARS-CoV-2 seroprevalence and asymptomatic viral carriage in healthcare workers: a cross-sectional study. Issue 12 (11th September 2020) - Shields, Adrian; Faustini, Sian E; Perez-Toledo, Marisol; Jossi, Sian; Aldera, Erin; Allen, Joel D; Al-Taei, Saly; Backhouse, Claire; Bosworth, Andrew; Dunbar, Lyndsey A; Ebanks, Daniel; Emmanuel, Beena; et al.
Abstract : Objective: To determine the rates of asymptomatic viral carriage and seroprevalence of SARS-CoV-2 antibodies in healthcare workers. Design: A cross-sectional study of asymptomatic healthcare workers undertaken on 24/25 April 2020. Setting: University Hospitals Birmingham NHS Foundation Trust (UHBFT), UK. Participants: 545 asymptomatic healthcare workers were recruited while at work. Participants were invited to participate via the UHBFT social media. Exclusion criteria included current symptoms consistent with COVID-19. No potential participants were excluded. Intervention: Participants volunteered a nasopharyngeal swab and a venous blood sample that were tested for SARS-CoV-2 RNA and anti-SARS-CoV-2 spike glycoprotein antibodies, respectively. Results were interpreted in the context of prior illnesses and the hospital departments in which participants worked. Main outcome measure: Proportion of participants demonstrating infection and positive SARS-CoV-2 serology. Results: The point prevalence of SARS-CoV-2 viral carriage was 2.4% (n=13/545). The overall seroprevalence of SARS-CoV-2 antibodies was 24.4% (n=126/516). Participants who reported prior symptomatic illness had higher seroprevalence (37.5% vs 17.1%, χ 2 =21.1034, p<0.0001) and quantitatively greater antibody responses than those who had remained asymptomatic. Seroprevalence was greatest among those working in housekeeping (34.5%), acute medicine (33.3%) and general internal medicine (30.3%), with lower rates observed in participants working in intensive care (14.8%). BAME (Black, Asian and minority ethnic) ethnicity was associated with a significantly increased risk of seropositivity (OR: 1.92, 95% CI 1.14 to 3.23, p=0.01). Working on the intensive care unit was associated with a significantly lower risk of seropositivity compared with working in other areas of the hospital (OR: 0.28, 95% CI 0.09 to 0.78, p=0.02). Conclusions and relevance: We identify differences in the occupational risk of exposure to SARS-CoV-2 between hospital departments and confirm asymptomatic seroconversion occurs in healthcare workers. Further investigation of these observations is required to inform future infection control and occupational health practices.